Multimodality Image Analysis in a Cohort of Patients with Atypical Juvenile Ocular Toxocariasis - Xiaohong Guo; Hui Liu; Manli Li; Ke Fan; Shuyin Li; Bo Lei (Journal of Ophthalmology)
Purpose. To analysis the multimodal imaging of a group of patients diagnosed clinically with atypical juvenile ocular toxocariasis (OT). Methods. In this case series study, we examined 9 young patients diagnosed with atypical OT. Routine ophthalmological examinations, fundus photography, optical-coherence tomography (OCT), fluorescein angiography (FFA), and B-mode ultrasound were performed. A questionnaire was used to record whether the patients were newly diagnosed and whether they had a history of exposure to a cat and dog. Aqueous humor and serum samples were taken for serological tests. Results. In all the patients, yellow-and-white dot-shaped lesions and perivascular white sheath were seen in the fundus. Heterogeneous changes including hyper-reflection in the disrupted neuroretina, hyper-reflection in the outer retinal layer, high-reflection mass on the surface of the neuroretina accompanied with reflective attenuation, and high-reflection mass involving the entire neuroretina or high-reflection mass in the vitreous body were noticed in OCT images. On FFA, seven of these patients (77.8%) showed leakage of fluorescein in the small- and medium-branch veins of the retina, and a “bristle-like” change indicated increased permeability of the vessels. B-mode ultrasound showed proliferative membranes and proliferative bands (33.3%), as well as spotted opacity in the vitreous (66.7%). The antibodies to Toxocara canis in the aqueous humor and serum were positive, and the Goldmann–Witmer coefficient was significantly increased in 6 out of 7 patients. Conclusions. Multimodality images are useful in the diagnosis of atypical juvenile OT, which could be easily overlooked and misdiagnosed.